Elements of real analysis - Al-Gwaiz, M.A. (19..-....); Elsanousi, S.A. (19..-....) (Pure and applied mathematics : a series of monographs and textbooks, 2007)
Requiring only basic knowledge of elementary calculus, this book presents the necessary material for a first course in real analysis. It covers three groups of main topics: the real number system, sequences, and series; functions, limits, continuity, and differentiability; and integration, including Riemann integrals. It also contains two chapters on Lebesgue integrals, a topic not usually covered at this level. It begins with the basic axioms of the real number system and gradually builds the basic core of real analysis. Developed by experts who teach such courses, this text is ideal for undergraduate students in mathematics and related disciplines such as engineering, statistics, computer science, and physics.